Monitoring system for electrical variables implementing blockchain and python - Giral Ramírez, Diego Armando; Muñoz Romero, Javier Andres; Ramírez Vanegas, Carlos Alberto (Tecnura, 2022)
Objective: This article presents one of the Blockchain applications in power systems employing the electrical variables monitoring delivered by a simulated relay. Methodology: The electrical variables are verified, compared, and uploaded to a blockchain network created by a network of servers; these are responsible for uploading, validating, and exporting information to the system. This study is carried out through the Python programming language. Results: An algorithm capable of integrating these variables from a simulated relay is created, 4 servers are created that are in charge of taking the relay signals every minute, validating that they are unique in the blockchain and uploading them, the first node that completes this task uploads its identification and the information of the relay, the processing times of the information once obtained are approximately 10 seconds Conclusions: It is concluded that the algorithm is capable of decentralizing the information collected by the servers in times equal to or greater than one minute, which can be very useful when saving information, in applications such as control by the network operator it falls short by having times greater than or equal to one minute, it should be taken into account that, for the development of a blockchain with a greater number of equipment, it is advisable to use machines with high levels of processing, much higher RAM memories, these characteristics allow the algorithm to run smoothly and in the shortest possible time. Financing: Universidad Distrital Francisco José de Caldas